DAMPAK KOMUNIKASI, STRES KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN TK-KB-TAA AL FATIHAH YOGYAKARTA - Yenni Kurnia Gusti; Astrilita Novia Ratnasari (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to determine and analyze the effect of communication, work stress, and motivation on performance in teachers and employees of TK-KB-TAA Al Fatihah Yogyakarta. This study uses a quantitative method, namely data collection using a questionnaire. The population in this study were all teachers and employees of TK-KB-TAA Al Fatihah Yogyakarta, totaling 50 people and the sample used in this study totaled 45 teachers and employees. The validity test indicates that the statements in this study are valid, while the reliability test using Cronbach Alpha is declared reliable. This study uses Multiple Linear Regression Analysis. The results of the analysis show that (1) Communication has a positive effect on employee performance, (2) Job Stress has a negative effect on employee performance, and (3) Motivation has a positive effect on employee performance.